Complicated Relationships. International Humanitarian Aid to Lithuania between 1919–1922 - Griffante, Andrea (History / Istorija, 2022)
Abstract. Lithuania was included in the scope of international humanitarian organizations in the early post-war period. Although the mission of the American Aid Administration, the American Red Cross and Lady Murielė Paget helped to alleviate Lithuania’s difficult social situation, humanitarian aid to Lithuania was provided without much enthusiasm. This was due to funding problems and political factors, as well as competition between international humanitarian organizations, and not always peaceful relations between the Lithuanian government and humanitarian organizations. Only Lady Paget’s mission has had closer ties with local authorities and long-term results.